Rola testosteronu w regeneracji mięśni szkieletowych po wysiłku fizycznym = Role of testosterone in skeletal muscle regeneration after physical effort - Morawin, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to introduce the up-to-date information on molecular mechanisms of skeletal muscle regeneration and the role of testosterone in regeneration and adaptation of skeletal muscles to physical effort.
Keywords: testosterone; stem cells; skeletal muscles; physical effort; testosteron; mięśnie szkieletowe; komórki macierzyste; wysiłek fizyczny